Refleksi Kepercayaan Kepala Sekolah: Studi Narative Inquiry Dalam Konteks Kepemimpinan - Hera Nuraini; Ilfi Johar Nafisah; Masduki Ahmad; Siti Zulaikha (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2022)
This research was conducted with three objectives, namely to find out (1) the principal's reflection on trust in the context of leadership; (2) The vice principal's reflection on trust in the context of being led; (3) The leadership relationship between the principal and the vice principal. The research method is a Narrative Inquiry Study and a qualitative approach. Participants consisted of the researchers themselves, teachers, vice principals and school principals. This research was conducted at SMKN 26 Pulo Gadung, East Jakarta. Data collection techniques with various types of field texts from photos, field notes, and transcripts of conversations to interview transcripts. Data analysis technique with resto-rying stage (telling back) and coding for themes (codification). Research results In terms of intrapersonal competence, principals are very confident to be able to analyze problems and opportunities. The type of leadership management in the school is participatory management and there is mutual trust from all structural members who are in charge and fulfill their respective responsibilities. If the leader's trust cannot be given, the organization's journey will be confused in determining the direction.